Perlindungan Hukum bagi Pemilik Rumah Kos Akibat PenyewaMengulangsewakan Kepada Pihak Ketiga dalam PerspektifHukum Positif Indonesia - suryati; Teguh Anindito (Faculty of Law, Universitas Wijayakusuma Purwokerto, 2024)
The rental agreement for the boarding house is a specialist in the rentalagreement, which is regulated in Article 1548 of the Civil Code. Theemergence of a boarding house rental agreement is based on the principleof freedom of contract which is regulated in Article 1338 paragraph 1 ofthe Civil Code. The rental agreement for renting a boarding house madeorally is indeed considered legally valid, because the Civil Code does notexplicitly specify the form of the rental agreement made by the parties. Thething that needs to be understood from an oral agreement is that it usuallyhas risks in the future. Even though the owner of the boarding house andthe prospective tenant have agreed not to return the rental of theboarding house to a third party, in reality there is still a transfer to a thirdparty. The purpose of this research is to find out the legal protection forthe owner of the boarding house due to the tenant repeating the rental ofthe boarding house to a third party. To achieve this goal, the writer uses asociological juridical approach; The research specification is descriptive.The data used in this study include primary data and secondary data.Primary data were obtained by free, guided interviews with owners andtenants. Secondary data in the form of the Civil Code; books by experts,research papers, scientific journals, internet, legal dictionaries. Thepresentation of data in the form of descriptions is arranged systematically.The data were analyzed qualitatively. Conclusion: Legal protection forboarding house owners due to tenants repeating boarding houses to thirdparties without asking permission and knowledge of the boarding houseowners, is to be able to cancel the rental agreement and claimcompensation based on Article 1559 of the Civil Code